2022
DOI: 10.3390/cells11193009
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and the Cybernetic Regulation of Ischemic Inflammatory Responses through PNC Formation Regulated by Extracellular Nucleotide Metabolism and Signaling

Abstract: Ischemic events are associated with severe inflammation and are here referred to as ischemic inflammatory response (IIR). Recent studies identified the formation of platelet–neutrophil complexes (PNC) as key players in IIR. We investigated the role of extracellular platelet nucleotide signaling in the context of IIR and defined a cybernetic circle, including description of feedback loops. Cybernetic circles seek to integrate different levels of information to understand how biological systems function. Our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…Recent studies have also suggested that SEMA7A could play a potential part in triggering inflammation in cases of lung injury induced by seawater aspiration ( 12 ) or following lipopolysaccharide challenge ( 13 ) and contribute to metabolic reprogramming in peritoneal macrophages ( 14 ). In a recent study, we were also able to show that PNCs (platelet–neutrophil complexes) are increased in patients with acute myocardial infarction and this is associated with increased levels of SEMA7A ( 15 , 16 ). However, controversial data exist for the role of SEMA7A in the intestinal system, since a study conducted by Kang et al.…”
Section: Introductionmentioning
confidence: 69%
“…Recent studies have also suggested that SEMA7A could play a potential part in triggering inflammation in cases of lung injury induced by seawater aspiration ( 12 ) or following lipopolysaccharide challenge ( 13 ) and contribute to metabolic reprogramming in peritoneal macrophages ( 14 ). In a recent study, we were also able to show that PNCs (platelet–neutrophil complexes) are increased in patients with acute myocardial infarction and this is associated with increased levels of SEMA7A ( 15 , 16 ). However, controversial data exist for the role of SEMA7A in the intestinal system, since a study conducted by Kang et al.…”
Section: Introductionmentioning
confidence: 69%
“…The involvement of platelets in the tumorigenesis of various malignancies has also been demonstrated 22 . Platelets tightly control the actions of neutrophils by forming platelet-neutrophil complexes in the blood and guiding neutrophils into ischemic tissues 23 . Additionally, leaky tumor vasculature allows direct interaction between platelets and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…PNCs were identified as CD45 + Ly-6G/C + CD41 + events and expressed as percentage of CD45 + Ly-6G/C + neutrophils. In addition, neutrophil numbers from PBS-treated samples were expressed as percentage of CD45 + leukocytes and compared between animals to rule out variations in blood composition [29].…”
Section: Measurement Of Pnc Formation In Vitromentioning
confidence: 99%
“…Thus, PNCs may contribute to both the thrombotic and inflammatory processes triggered by mIRI [75,89], which is also reflected by increased numbers of circulating PNCs in the blood of patients with acute coronary syndrome [58,65,74]. Furthermore, the number of PNCs in ischemic myocardial tissue correlated with the extent of IIR and mIRI in animal studies [29,50].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation